2020
DOI: 10.23736/s0022-4707.19.09668-3
|View full text |Cite
|
Sign up to set email alerts
|

The metabolic demand of external load carriage in golfers: a comparison of a single versus double-strap golf bag

Abstract: The version presented here may differ from the published version or, version of record, if you wish to cite this item you are advised to consult the publisher's version. Please see the 'permanent WRaP URL' above for details on accessing the published version and note that access may require a subscription.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 38 publications
0
5
0
2
Order By: Relevance
“…Additionally, a previous study indicated that cardiovascular stress, including HR, was 10% greater when a single bag was carried at the chest than that when held at the sides of the body [1]. Furthermore, carrying a double-strap bag (golf bag) might require less VdotO2 and require a lower HR than a single-strap bag [12]. In this study, cardiac responses did not vary based on bag carrying method, even for one-handed bag carrying (VH).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a previous study indicated that cardiovascular stress, including HR, was 10% greater when a single bag was carried at the chest than that when held at the sides of the body [1]. Furthermore, carrying a double-strap bag (golf bag) might require less VdotO2 and require a lower HR than a single-strap bag [12]. In this study, cardiac responses did not vary based on bag carrying method, even for one-handed bag carrying (VH).…”
Section: Discussionmentioning
confidence: 99%
“…A 2017 article on physical activity accrued while playing golf in the British Medical Journal by Luscombe et al reviewed 19 studies. Five studies had both energy expenditure and distance walked during the round of golf with using either a cart or carrying the clubs as an endpoint [8,[14][15][16][17]. The articles were reviewed for course yardage and a google search was used to find the current course length.…”
Section: Distancementioning
confidence: 99%
“…Two studies were conducted on the metabolic cost of carrying golf clubs in a single bag while walking on a treadmill. Holland and Godwin [11], using 16 male recreational golfers, found that carrying a 12.5 kg double-strap golf bag resulted in less metabolic stress (e.g., oxygen cost, HR) than carrying a single-strap bag. Ikeda et al [12] found similar results in a comparable study with 15 males.…”
Section: Current State Of Knowledgementioning
confidence: 99%